Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

The matrix equation represents a system of equations.

[tex]\[
\left[\begin{array}{ll}
2 & 7 \\
2 & 6
\end{array}\right]\left[\begin{array}{l}
x \\
y
\end{array}\right]=\left[\begin{array}{l}
4 \\
6
\end{array}\right]
\][/tex]

Solve for [tex]\( y \)[/tex] using matrices. Show or explain all necessary steps.


Sagot :

To solve the matrix equation

[tex]\[ \left[\begin{array}{cc} 2 & 7 \\ 2 & 6 \end{array}\right]\left[\begin{array}{c} x \\ y \end{array}\right]=\left[\begin{array}{c} 4 \\ 6 \end{array}\right], \][/tex]

we will use the inverse of the coefficient matrix.

### Step 1: Define the matrices

Let [tex]\( A \)[/tex] be the coefficient matrix, [tex]\( \mathbf{x} \)[/tex] be the variable vector, and [tex]\( \mathbf{b} \)[/tex] be the constant vector.

[tex]\[ A = \left[\begin{array}{cc} 2 & 7 \\ 2 & 6 \end{array}\right], \quad \mathbf{x} = \left[\begin{array}{c} x \\ y \end{array}\right], \quad \mathbf{b} = \left[\begin{array}{c} 4 \\ 6 \end{array}\right] \][/tex]

### Step 2: Calculate the inverse of matrix [tex]\( A \)[/tex]

We need to find [tex]\( A^{-1} \)[/tex], the inverse of matrix [tex]\( A \)[/tex]. Recall that if [tex]\( A \)[/tex] is a 2x2 matrix

[tex]\[ A = \left[\begin{array}{cc} a & b \\ c & d \end{array}\right], \][/tex]

then the inverse [tex]\( A^{-1} \)[/tex] is given by

[tex]\[ A^{-1} = \frac{1}{ad - bc} \left[\begin{array}{cc} d & -b \\ -c & a \end{array}\right] \][/tex]

For our matrix [tex]\( A \)[/tex]:

[tex]\[ a = 2, \quad b = 7, \quad c = 2, \quad d = 6 \][/tex]

First, calculate the determinant [tex]\( \text{det}(A) \)[/tex]:

[tex]\[ \text{det}(A) = ad - bc = (2)(6) - (2)(7) = 12 - 14 = -2 \][/tex]

Now, calculate [tex]\( A^{-1} \)[/tex]:

[tex]\[ A^{-1} = \frac{1}{-2} \left[\begin{array}{cc} 6 & -7 \\ -2 & 2 \end{array}\right] = \left[\begin{array}{cc} -3 & \frac{7}{2} \\ 1 & -1 \end{array}\right] = \left[\begin{array}{cc} -3 & 3.5 \\ 1 & -1 \end{array}\right] \][/tex]

### Step 3: Multiply [tex]\( A^{-1} \)[/tex] by [tex]\( \mathbf{b} \)[/tex]

To find the vector [tex]\( \mathbf{x} \)[/tex], multiply [tex]\( A^{-1} \)[/tex] by [tex]\( \mathbf{b} \)[/tex]:

[tex]\[ \mathbf{x} = A^{-1} \mathbf{b} \][/tex]

Perform the matrix multiplication:

[tex]\[ \mathbf{x} = \left[\begin{array}{cc} -3 & 3.5 \\ 1 & -1 \end{array}\right] \left[\begin{array}{c} 4 \\ 6 \end{array}\right] \][/tex]

Calculate each component of [tex]\( \mathbf{x} \)[/tex]:

1. For [tex]\( x \)[/tex]:

[tex]\[ x = (-3)(4) + (3.5)(6) = -12 + 21 = 9 \][/tex]

2. For [tex]\( y \)[/tex]:

[tex]\[ y = (1)(4) + (-1)(6) = 4 - 6 = -2 \][/tex]

### Step 4: Verify the solution [tex]\( x = 9 \)[/tex] and [tex]\( y = -2 \)[/tex]

Thus, the solution to the system of equations is:

[tex]\[ x = 9, \quad y = -2 \][/tex]

So, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy the given matrix equation are [tex]\( x = 9 \)[/tex] and [tex]\( y = -2 \)[/tex]. The inverse matrix [tex]\( A^{-1} \)[/tex] is

[tex]\[ \left[\begin{array}{cc} -3 & 3.5 \\ 1 & -1 \end{array}\right] \][/tex]

and the result calculated using the inverse is:

[tex]\[ \begin{pmatrix} 9 \\ -2 \end{pmatrix}. \][/tex]